Human influenza viruses in South-East and East Asia: a systematic review of seasonal patterns, viral types/subtypes, and antiviral susceptibility pattern in the past two decades - Iribhogbe, Osede Ignis; Samuel, Sunday Olowo; Ohaju-Obodo, John O. (International Journal of Basic & Clinical Pharmacology, 2020)
The study aims to evaluate influenza seasonality pattern and identify influenza viral types/subtype as well as their antiviral susceptibility pattern in South-East (SE) and East Asia (E-Asia) with the view of providing useful information for public health action. The study is a systematic review of existing literature involving the use of search engines such as Google Scholar, PubMed and EBSCOHOST. The search was conducted using a multi-stage approach which yielded 66 articles after screening for relevance to the subject using specific inclusion and exclusion criteria. A total of 60 articles were eventually analyzed and the findings were presented in tables and bar charts. The study showed that the influenza virus was more prevalent in the 6-20 years age group (SE: 53.3% and E-Asia: 44.8%) and also occurred commonly in the age of 61-90 years age group (SE: 15.6% and E-Asia: 24.1%). Seasonal peaks were reported more in the winter period with influenza A (H1N1) pdm09 (22.37%; 24.14%), seasonal influenza A (H1N1) (6.58%; 17.24%), A (H3N2) (11.84%; 17.24%), and influenza B Victoria/Yamagata (5.26%; 20.69%) being the predominant viral type/subtypes. The pathogenic avian influenza strains; AH5N1 (7.89%) and A (H7N9) (6.90%) was also reported in SE and E-Asia respectively. Oseltamivir (37.5%) and peramivir (37.04%) were the most frequently used anti-influenza agents in SE and E-Asia respectively. However, an H55Y+I436N combined mutation 4 (12.5%) and an H274Y amino acid substitution 5 (18.5%) in the neuraminidase gene of influenza A (H1N1) pdm09 was associated with decreased sensitivity to neuraminidase inhibitors. The study has shown that influenza A (H1N1) pandemic and seasonal strain, A (H3N2), and B Victoria/Yamagata remains the predominant circulating virus in SE and E-Asia. However, the dynamic antigenic and genetic evolution of the virus calls for more frequent surveillance in the region.